Non-Intubated Thoracic Surgery: Standpoints and Perspectives - Anile, Marco; Vannucci, Jacopo; Ferrante, Francesco; Bruno, Katia; De Paolo, Dalila; Bassi, Massimiliano; Pugliese, Francesco; Venuta, Federico; , the NIVATS Interest Group; Diso, Daniele; Poggi, Camilla; Pecoraro, Ylenia; et al. (Frontiers in Surgery, 2022)
Non-intubated video-assisted thoracic surgery (NI-VATS) combines the advantages of a non-intubated surgery with the benefits of a minimally invasive approach. At first, NI-VATS was performed in case of fragile patients when general anesthesia and/or orotracheal intubation could be foreseen unconvinient. However, NI-VATS indications have been incrisingly extended to different patient conditions considering the more and more assessed safety and feasibility of the procedure. Currently, NI-VATS approach is worldwide used for different thoracic surgery procedures including management of malignant pleural effusion, surgical treatment of empyema, anatomical and non-anatomical lung resection and other indications. In fact, this approach has shown to be less impactful than VATS under general anesthesia allowing for shorten hospitalization and faster recovery after surgery. Besides, NI-VATS is associated to fewer pulmonary complications, less respiratory distress and a mild systemic inflammatory reaction. For these reasons, this approach should be considered not only in patients with poor cardiac or respiratory function (general functional reserve), but in other eligible conditions also. We explored the anestethic and surgical aspects of such approach including the management of analgesia, cough reflex, depth of sedation and intraoperative technical issues to put this thechnique in perspective.